A comparative study on the effectiveness of 3R (Reuse, Reduce and Recycle) programme among primary school students in Tumpat, Kelantan - Mohd Zain, Norhasmah; Anua, Siti Marwanis; Marzuki, Nursalwana Sofea; Abdul Rahman, Haliza (Human Resource Management Academic Research Society, 2022)
Currently, awareness towards environmental protection is increasing especially among young generation. However, such awareness initiative was still could not provide an impactful output towards environment. Hence this study was conducted to evaluate the effectiveness of 3R programme in primary schools by comparing the levels of knowledge, attitude and practices (KAP) on 3R between school with 3R programme and school without 3R programme. A cross sectional study was performed among 310 primary school students at Sekolah Kebangsaan Chabang Empat and Sekolah Kebangsaan Padang Pohon Tanjung. A validated questionnaire consist of sociodemographic data, knowledge, attitude and practice was distributed to respondents by systematic random sampling. Results showed that, school with 3R programme has a good knowledge (72.3%) and practice (47.7%). Meanwhile, school without 3R programme obtained high percentage in good attitude level (87.7%). Moreover, there were significant differences (p<0.05) in both knowledge and practice scores between school with 3R programme and school without 3R programme. Across gender, both knowledge and practice scores were significantly different (p<0.05) among female students between school with 3R programme and school without 3R programme. The attitude and practice scores were significantly different between school with 3R programme and school without 3R programme among students in level 1 (p<0.05). Whereas, knowledge score was significantly different between the two schools among students in level 2 (p=0.001). There were significant relationships between knowledge and attitude, between knowledge and practice and between attitude and practice for both schools however the correlations were positive and stronger for students in school with 3R programme compared to school without 3R programme. In conclusion, all primary school students should be given continuous awareness on 3R to increase their attitude and practice. The exposure given should be in different approach based on gender and standard level aspect.